2006
DOI: 10.1038/sj.mp.4001868
|View full text |Cite
|
Sign up to set email alerts
|

The SNAP-25 gene is associated with cognitive ability: evidence from a family-based study in two independent Dutch cohorts

Abstract: The synaptosomal-associated protein of 25 kDa (SNAP-25) gene plays an integral role in synaptic transmission, and is differentially expressed in the mammalian brain in the neocortex, hippocampus, anterior thalamic nuclei, substantia nigra and cerebellar granular cells. Recent studies have suggested a possible involvement of SNAP-25 in learning and memory, both of which are key components of human intelligence. In addition, the SNAP-25 gene lies in a linkage area implicated previously in human intelligence. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 50 publications
2
63
0
1
Order By: Relevance
“…The derived, human specific allele in the beta-2 adrenergic receptor (rs1042713) is known to reduce agonist induced down-regulation of receptor density and was found to increase cognitive ability in the young Dutch cohort but was associated with a decrease in the Scottish cohort at age 70. The contrasting results for the age groups *12, *37 and 70 years for this functional variant are similar to the effect of a mutation in the brain-derived neurotrophic factor shown to be associated with age-related change in reasoning skills (Harris et al 2006) and might be explained by the observation that different age classes are known to differ in the genetic architecture of cognitive ability reflected in different heritability estimates (see Gosso et al 2006). A similar shift in monoaminergic neurotransmission with ageing is seen for dopaminergic systems regulated by catechol-O-methyltransferase.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The derived, human specific allele in the beta-2 adrenergic receptor (rs1042713) is known to reduce agonist induced down-regulation of receptor density and was found to increase cognitive ability in the young Dutch cohort but was associated with a decrease in the Scottish cohort at age 70. The contrasting results for the age groups *12, *37 and 70 years for this functional variant are similar to the effect of a mutation in the brain-derived neurotrophic factor shown to be associated with age-related change in reasoning skills (Harris et al 2006) and might be explained by the observation that different age classes are known to differ in the genetic architecture of cognitive ability reflected in different heritability estimates (see Gosso et al 2006). A similar shift in monoaminergic neurotransmission with ageing is seen for dopaminergic systems regulated by catechol-O-methyltransferase.…”
Section: Discussionmentioning
confidence: 89%
“…The QTDT software package was used to perform a family-based association analysis in two Dutch cohorts phenotyped for several measures of cognitive ability (for details see below and Gosso et al 2006). IQ data were corrected for age and sex, and all analyses were performed while modeling the environmental and (poly-) genetic components of variance.…”
Section: Genetic Associationmentioning
confidence: 99%
“…Results on cognitive effects of two other genes are described elsewhere. 39,40 Statistical analyses Allele frequencies of the COMT Val 108/158 Met and DRD2 A1/A2 polymorphisms were estimated in both cohorts using Haploview (http://www.broad. mit.edu/mpg/haploview), in which a Hardy -Weinberg test is implemented, based on an exact calculation of the probability of observing a certain number of heterozygotes conditional on the number of copies of the minor SNP allele.…”
Section: Adult Cohortmentioning
confidence: 99%
“…This SNAP-25 modulated mechanism might influence the hippocampal function. It is possible, therefore, that the reported association of SNAP-25 genotype with memory consolidation (Hou et al 2004) and long-term memory formation (Hou et al 2006) in rats as well as cognitive ability in humans (Gosso et al 2006) is caused by its influence on hippocampal function.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, animal studies showed that the hippocampal SNAP-25 protein is involved in memory consolidation and long-term memory formation in rats (Hou et al 2004(Hou et al , 2006. In humans it has been shown recently that the SNAP-25 gene is associated with the cognitive ability of healthy individuals (Gosso et al 2006). …”
Section: Introductionmentioning
confidence: 99%